The persistence of accountant beancounter images in popular culture. Issue 6 (19th June 2020) - Christensen, Mark; Rocher, Sébastien
Abstract : Purpose: In analysing the beancounter image's trajectory, from its birth to its persistence, in European French language comics between 1945 and 2016, this paper explores why artists continue beancounter image usage in popular culture. Design/methodology/approach: Beancounter characters have been studied in an application of Iconology (Panofsky, 1955) in order to unravel how individuals make sense of cultural artefacts and how, in turn, the visuals shape cultural belief systems at a given time. Findings: This study reveals that comics artists usage of the beancounter image results from their critical reactions to management and capitalism whilst at other times the usage is an indication of authenticity. Motivation for the usage is not constant over time nor is the impact of the beancounter image. Both appear dependant of the level of artistic freedom experienced by the artist. Research limitations/implications: Based on a single media (comics) with a unique characters (European French language) this study deepens exploration of the ways in which accounting becomes entwined with the everyday and implies that further research is needed. Originality/value: Extends the work of Smith and Jacobs (2011) and Jacobs and Evans (2012) by focusing on a genre of popular culture over a long period, and by adopting a critical viewpoint. Also expands the possible applications of Panofsky's (1955) Iconology in accounting studies.